Implementation of induction motor control and monitoring system for blower drive based on Internet of Things - Muhammad Zein, Habibi; Yuhendri, Muldi (Journal of Industrial Automation and Electrical Engineering, 2025)
Induction motors are widely used in industrial applications, particularly as blower drives, due to their simplicity, durability, and high efficiency. However, when operated at constant speed without considering load conditions, these motors often cause excessive energy consumption and reduced operational lifespan. This study develops an Internet of Things (IoT)-based control and monitoring system for a three-phase induction motor driving a blower by integrating Siemens Sinamics G120 Variable Speed Drive (VSD), Simatic S7-1200 PLC, SIMATIC KTP 700 HMI, and a web interface based on Node-RED. The system supports manual and automatic operation modes, with the automatic mode controlled by real-time ambient temperature readings from an LM35 sensor. The automatic control logic ensures the motor operates only when the temperature is within the range of 20°C to 37°C, automatically shutting down the motor if the temperature falls outside this range to prevent damage and inefficient operation, while the motor speed is proportionally adjusted according to the temperature within the specified range. Monitoring and control can be performed remotely via PC or smartphone using Ethernet communication based on the Profinet protocol. Testing results show that motor speed and direction can be accurately controlled and monitored in real time, with consistent data among the HMI, VSD, and external measuring instruments. This solution offers a reliable, user-friendly, and energy-efficient method for blower control in industrial environments, making a significant contribution to industrial automation by combining conventional control systems with IoT technology